Does the white coat influence satisfaction, trust and empathy in the doctor–patient relationship in the General and Family Medicine consultation? Interventional study. Issue 12 (22nd December 2021) - Marques Caetano Carreira, Leonor; Dinis, Sara; Correia, António; Pereira, António; Belo, Regina; Madanelo, Inês; Brito, David; Gomes, Rita; Monteiro, Luís; Correia, Gil; Maia, Conceição; Marques, Tiago; et al.
Abstract : Objectives: To understand the influence of the white coat on patient satisfaction, opinions about medical clothing, perception about confidence, empathy and medical knowledge and the satisfaction and comfort level of physicians in consultation. Setting: An interventional study was conducted with a representative sample of the population attending primary care in central Portugal. Participants: The sample was composed by 286 patients divided into two groups exposed or not to a doctor wearing a white coat. The first and last patients in consultation every day for 10 consecutive days were included. Interventions: Every other day the volunteer physicians consulted with or without the use of a white coat. At the end of the consultation, a questionnaire was distributed to the patient with simple questions with a Likert scale response, the Portuguese version of the 'Trust in physician' scale and the Jefferson Scale of Patient Perceptions of Physician Empathy - Portuguese Version (JSPPPE-VP scale). A questionnaire was also distributed to the physician. Outcomes: Planned and measured primary outcomes were patient satisfaction, trust and perception about empathy and secondary outcomes were opinion about medical clothing, satisfaction and comfort level of physicians in consultation. Results: The sample was homogeneous in terms of sociodemographic variables. There were no statistically significant differences between the groups in terms of satisfaction, trust, empathy and knowledge perceived by the patients. There were differences in the opinion of the patients about the white coat, and when the physician was wearing the white coat this group of patients tended to think that this was the only acceptable attire for the physician (p<0.001). But when the family physician was in consultation without the white coat, this group of patients tended to agree that communication was easier (p=0.001). Conclusions: There was no significant impact of the white coat in patient satisfaction, empathy and confidence in the family physician. Trial registration number: ClinicalTrials.gov ID number: NCT03965416 .